Her Parasites: A poetic ecospiritual perspective of the COVID-19 pandemic and nature's intelligence - Kolandai, Komathi (Journal of Ecohumanism, 2024)
In this transdisciplinary perspective, I present my initial ecospiritual thinking about the COVID-19 pandemic in a poem, titled Her Parasites. I identify with other thinkers â€“ both those in science and not â€“ who articulated ecophilosophical musings about the pandemic in various ways, some of whom were met with mockery and censure. In the hope that it will inspire openness and a sense of curiosity, I draw on metaphysical insights from Vedic treatises and the literature on environmental decline, zoonotic epidemiology, health science, animal agriculture, animal ethics, and animal sentience to explain my poemâ€™s philosophical and ecological framework. I focus on the scientific knowledge of epidemics caused by viruses that transcend species boundaries, why cross-species hopping occurs, and the nature (and incredible intelligence) of such viruses. I invite readers to consider ancient Vedic principles that articulate the rationale for living harmoniously with other sentient beings and entities. Considering the unseen metaphysical association between the pandemic and animal cruelty explained through the Vedic laws of KarmÄ, I present the possibility that one of the lessons Mother Earth might have wanted the Homo sapiens species to learn from the COVID-19 pandemic is its need to alter its diet. I end with a discussion on the possibility and value of this change. The downplaying or denial of animal sentience (strategies to overcome the psychological discomfort of incongruence between loving animals and eating them, as described in social psychology), is a barrier to this change. However, observed through a Vedic lens, this cognitive dissonance suggests that the Homo sapiens species is innately humane, the realisation of which might hold the key to this dietary change.